2020
DOI: 10.1007/s00167-020-06220-0
|View full text |Cite
|
Sign up to set email alerts
|

Low surgical routine increases revision rates after quadriceps tendon autograft for anterior cruciate ligament reconstruction: results from the Danish Knee Ligament Reconstruction Registry

Abstract: Low department routine increases revision rates after quadriceps tendon autograft for anterior cruciate ligament reconstruction -results from the DanishKnee Ligament Reconstruction Registry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
36
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 40 publications
(40 citation statements)
references
References 26 publications
4
36
0
Order By: Relevance
“…This ethos may have some merit when reviewing the Danish registry outcomes where Lind et al reported a high graft failure rate (6.4%) in ACLR with QT autograft by low volume ACLR centres (< 100 QT autograft ACLR) and comparable graft failure rates between QT autograft ACLR in high volume centres (> 100 ACLR) (2.9%), HT autograft (2.2%) and PT autograft (3.7%). 43 Surgeons should therefore maintain expertise in several techniques or refer patients to another specialist if the patient requests or needs an alternative graft choice.…”
Section: Discussionmentioning
confidence: 99%
“…This ethos may have some merit when reviewing the Danish registry outcomes where Lind et al reported a high graft failure rate (6.4%) in ACLR with QT autograft by low volume ACLR centres (< 100 QT autograft ACLR) and comparable graft failure rates between QT autograft ACLR in high volume centres (> 100 ACLR) (2.9%), HT autograft (2.2%) and PT autograft (3.7%). 43 Surgeons should therefore maintain expertise in several techniques or refer patients to another specialist if the patient requests or needs an alternative graft choice.…”
Section: Discussionmentioning
confidence: 99%
“…A registry study published by Lind et al 21 showed higher failure rates for quadriceps tendon versus HT, but a study published shortly afterward by the same study group demonstrated that high-activity clinics, defined as clinics that performed >100 ACLRs per year, showed similar revision outcomes for quadriceps, hamstrings, and patellar tendon grafts, while clinics that performed <100 ACLRs (low-activity clinics) showed higher failure rates for quadriceps grafts. 20 They concluded that the higher failure rates for quadriceps tendon autografts could be due to a lower surgical routine in low-activity clinics. 20 A recent study by our research group in a different study population showed lower, but not statistically significant, failure rates for quadriceps tendon versus HT or BPB (N = 111; failure rates: Quad, 6.7%, HT, 9.4%, BPB, 18.8%).…”
Section: Discussionmentioning
confidence: 99%
“… 20 They concluded that the higher failure rates for quadriceps tendon autografts could be due to a lower surgical routine in low-activity clinics. 20 A recent study by our research group in a different study population showed lower, but not statistically significant, failure rates for quadriceps tendon versus HT or BPB (N = 111; failure rates: Quad, 6.7%, HT, 9.4%, BPB, 18.8%). 2 In the largest cohort study published to date by Runer et al, 34 a significantly higher risk of revision surgery was reported for HT autografts.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, a follow-up study by the same group evaluated low- and high-volume ACL surgery centers and reported on similar failure rates for both the QT (2.9%) and BPTB (2.3%) for high-volume centers. 23 Widner et al 35 compared large cohorts of QT, BPTB, and hamstring tendon autografts and found no significant differences in failure rates.…”
Section: Discussionmentioning
confidence: 99%